Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1093/jnci/95.8.605
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Double-Blind Placebo-Controlled Trial of Bestatin in Patients With Resected Stage I Squamous-Cell Lung Carcinoma

Abstract: Survival was statistically significantly better for patients with completely resected stage I squamous-cell lung carcinoma who were treated with bestatin as a postoperative adjuvant therapy than for those who received a placebo. This result requires confirmation in other phase III trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(72 citation statements)
references
References 35 publications
1
71
0
Order By: Relevance
“…All of these mechanisms are postulated to result in myeloma cell death, particularly as malignant cells are often more dependent on the availability of amino acids such as arginine. There is a precedent for taking such an approach in hematologic cancers, as bestatin, a broad-spectrum inhibitor of the aminopeptidases, has been shown to be effective in Japan in solid tumors and leukemia and is well tolerated in clinical trials (13,14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All of these mechanisms are postulated to result in myeloma cell death, particularly as malignant cells are often more dependent on the availability of amino acids such as arginine. There is a precedent for taking such an approach in hematologic cancers, as bestatin, a broad-spectrum inhibitor of the aminopeptidases, has been shown to be effective in Japan in solid tumors and leukemia and is well tolerated in clinical trials (13,14).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, many tumor cells are dependent on specific amino acids and previous studies have shown that depletion of these amino acids has a greater effect on cancer cells than normal cells (11,12). Evidence for the clinical value of such an approach is seen from the use of bestatin, a broad-range inhibitor of aminopeptidases, which has been used for over a decade in Japan for the treatment of acute and chronic acute myeloid leukemia (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Ichinose et al showed that bestatin had a therapeutic effect of prolonging survival when used as a postoperative adjuvant treatment for patients whose stage I squamous-cell carcinoma was completely resected. 38 Likewise, APN/CD13-targeting treatment such as bestatin combined with paclitaxel-based chemotherapy may lead to better prognosis of OVCA patients. Although further clarification of the mechanism and function of APN/CD13 in tumor biology is essential, APN/CD13 may become a novel therapeutic target for OVCA.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from antioxidant activity, this compound showed selective cytotoxicity in cancer cells. 20 and 24 lg/mL phenazine brought abount IC 50 in HeLa and MCF-7 cell lines respectively (Fig. 3).…”
Section: Assay Of Free Radical Scavenging and Cytotoxicitymentioning
confidence: 91%
“…Clinical trials of cancer therapies in combination with aminopeptidase inhibitors are in progress. Bestatin is an example of aminopeptidase inhibitor used to treat acute and chronic acute myeloid leukemia under the trademark Ubenimex in Japan [20]. It is possible that a bioactive that is inhibitory to Streptomyces aminopeptidase can be inhibitory to eukaryotic aminopeptidases too.…”
Section: Aminopeptidase Inhibitory Activitymentioning
confidence: 99%